TANFIZU ANTTORIQATU AL ISTIQRAIYYAH FII TA’LIMI ANNAHWI ‎LITTHOLIBAATS ASSANATURABIAH BITARBIYYATI MUA’ALLIMIN ‎AL ISLAMIYAH PERINDUAN SUMENEP MADURA - Asmaniyah Siroj; Eli Safitri (Universitas Islam Negeri Imam bonjol Padang, 2022)
The Institute of Islamic Teachers Education Brendoan Somenep Madura is one of the modern educational institutions that teach religious sciences using the Arabic language, such as jurisprudence, monotheism, beliefs, ethics, etc., and that grammar is the basis for understanding Arabic texts, which has many factors for understanding Islamic materials that are explained in Arabic and thus increase The importance of studying it. Thus, teaching grammar aims to develop students' understanding so that they can provide examples of grammar that the teacher explained during the teaching process. The objectives of this research are: 1) to find out the implementation of the inductive method in teaching grammar to the fourth year students of Islamic teacher education at the Islamic Institute of Al-Amin Brendwan Sominb Madura 2) to find out the supporting factors and obstacles to the implementation of the inductive method in teaching grammar to the fourth year students of Islamic teacher education at the Islamic Institute of Al-Ameen Brendwan Somnab Madura. In this research, the researcher used the qualitative approach using the descriptive approach, and the method of all research used in this research is interview, observation and documents. The result of the research is: 1) Implementation of the inductive method in teaching grammar for fourth year students of Islamic teacher education at the Al-Ameen Islamic Institute in Brindwan. 2) The supporting factors in implementing the inductive method in teaching grammar are: the students' speed of understanding, the actual joint students. As for the obstacle factors in implementing the inductive method in teaching grammar, they are: lack of vocabulary mastery for female students, failure to provide various examples from the teacher